Cross-sectional study assessing HIV-related knowledge, attitudes and behavior in the Namibian truck transport sector: Readjusting HIV prevention programs in the workplace. Issue 4 (July 2015) - Kiderlen, Til R.; Conteh, Michael; Roll, Stephanie; Seeling, Stefanie; Weinmann, Stefan
Summary The objectives of this study were to assess the current status of HIV-related knowledge, attitudes, and behavior (KAB) of employees in the private transport sector in Namibia and to compare companies with established HIV workplace program (WPPs) with those that have recently initiated the implementation of such programs. The study was designed as a cross-sectional questionnaire-based survey. Between January and March 2011, the survey was conducted in the Namibian truck transport sector in six companies of different sizes. The participants were selected randomly from the workforce. Data collection was based on a KAB questionnaire. The range of correct answers to the survey concerning the knowledge of HIV transmission was 67–95%. Twenty percent of the employees had never been tested for HIV. Additionally, risky sexual behaviors were quite prevalent and included having multiple concurrent partners and the use of sex for incentives. This study revealed that drivers and laborers were especially at risk for such behaviors. The employees of companies with established WPPs were tested for HIV more often than those of companies with new WPPs; however, aside from this difference, only minor differences were observed between the two groups. The findings of this study highlight the need for on-going HIV information and prevention campaigns that focus on the special needs of mobile and low-income workers. WPPs should be tailored accordingly and shift their focus to more practical approaches, such as voluntary counseling and testing (VCT), to increase their effectiveness.